Successful management of a case of dystocia due to breech presentation in non-descript cattle: A case study - Sasidharan, Jisna Kuttiyeri; Gupta, Shashikant; Dangi, Pradeep; Chandra, Pradeep; Jackson, Amala; Jasrotia, Nancy; Kumar, Brijesh; Ghosh , Subrata Kumar (The Indian Journal of Animal Reproduction, 2023)
A case of fetal dystocia due to breech presentation in non-descript cattle was presented to the outpatient department of veterinary gynaecology and obstetrics, Teaching Veterinary Clinical Complex-Referral Veterinary Polyclinic (TVCC-RVP), IVRI with anamnesis of the animal completed gestation and water bag ruptured normally without making any progress toward calving. Per-vaginal examination of the cow revealed fetal tail in birth canal and bilateral hip flexion (breech presentation).The dystocia relieved by obstetrical mutations. The cow was administrated with parenteral antibiotics, anti-inflammatory drugs, multivitamin supplements, along with ecobolics.